Deconstructing Hegel's sign-making imagination : Derrida and the textual imagination - Raftery-Skehan, Mark (Trinity College (Dublin, Ireland). Department of French, 2012)
Following the identification of ways in which deconstruction and imagination suggest the possibility of shedding light upon one another, I seek to overcome certain objections to the notion of a textual or deconstructive imagination emanating from Husserlian or Platonist models, by addressing questions of language's origination and creativity within the context of Hegel's inchoate and problematic notion of a signmaking imagination.
Keywords: French, Ph.D.; Ph.D. Trinity College Dublin.